Pragmatismo e Humanitarismo: a política externa brasileira e a causa armênia (1912-1922) - Loureiro, Heitor de Andrade Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In the 1910s, Brazilian audience heard, for the first time, about the ‘Armenian Cause’ through the work of the intellectual Etienne Brasil. At that time, Brasil published several articles through the press and scientific societies in Rio de Janeiro, in which he portrayed the Armenians as Christian people from the East which had suffered all types of persecutions by the hands of the Turk-Muslims within the Ottoman Empire. Brasil’s reports were Orientalist in nature, largely spread in western thought at the time as a way of appealing to the Brazilian readership and decision-makers in order to support Armenians to create the Armenian Republic. When Armenia became independent, in 1918, Etienne Brasil became the first Armenian diplomatic representative in South America, which provided him an opportunity to address his appeals to the Brazilian presidency and to the Minister of External Relations in search of support to sustain the fragile republic whose population was majority composed by refugees, and survivors of the genocide perpetrated by the Ottoman government after 1915. This research aims to examine how the “Armenian cause” – range of juridical demands of the Armenian people within the international system – arrived in Brazil and became part of the Brazilian foreign policy agenda. Armenian demands were incorporated on this policy agenda by a small interest group that had been able to obtain access to decision-makers through personal connections and intensive press propaganda. Brazil was trying to realign itself within the international system as a key player after the Great War. In this context, the Armenian cause was presented by Etienne Brasil as an opportunity to show to the Powers that Brazil was ready to deal with challenges in that new global scenario and, therefore, deserved the prominent place that it had received at the Paris Peace Conference in 1919 and at the League of Nations. The hypothesis is that Brazilian support towards the Armenian Cause was a Pessoa administration’s pragmatic act that sought, through a humanitarian agenda, to gain prestige at the global level. However, this did not happen proactively. The Brazilian government responded to the pressure of this group of Armenians living in Rio de Janeiro and the American moves at the international arena. As such, this group worked as part of a diaspora acting as a transnational power, which could take advantage of the Brazilian political system’s porosity to influence Brazil’s agenda. The methodology consisted in analyzing files and documents from archives in Brazil and abroad to reconstitute the negotiations between Armenians and Brazilians in order to get the latter to support the former at the international fora, as well as analyzing the Rio de Janeiro’s press in the 1910-20s, which were a tool to sensitize public opinion to push Brazil to take action. In the late 1920, the Brazilian government finally accepted to act as mediator in the conflict between Armenians and Turks imbued with the modern humanitarianism ideas, but guided by the pragmatism and desire for prestige in the international system.

Հայկական հարցի մասին Բրազիլիայի հանրությունն առաջին անգամ տեղեկացել է 1910-ականներին` մտավորական Էթիէն Պրազիլի աշխատանքների միջոցով: Նշված ժամանակհատվածում Բրազիլը հրատարակել է մի շարք հոդվածներ Ռիո դե Ժանեյրոյի պարբերական մամուլի և գիտական հանրության միջոցով, որոնցում նա նկարագել է հայերին որպես Արևելքի քրիստոնյաների, ովքեր տառապել են բոլոր տեսակի հալածանքներից` Օսմանյան կայսրության թուրք մուսուլմանների ձեռքին: Բրազիլի հրապարակումներն իրենց էությամբ օրիենտալիստական էին, ինչը լայնորեն տարածված էր այդ շրջանում արևմտյան մտածողության մեջ` իբրև միջոց ազդելու Բրազիլիայի ընթերցողների և որոշում կայացնողների վրա, որպեսզի վերջիններս օգնեն հայերին հիմնելու Հայաստանի Հանրապետություն: Երբ 1918 թվականին Հայաստանն անկախացավ, Էթիէն Պրազիլը դարձավ առաջին հայ դիվանագիտական ներկայացուցիչն Հարավային Ամերիկայում, ինչն էլ իրեն հնարավորություն ընձեռեց իր խնդրագրերն հասցեագրել Բրազիլիայի նախագահությանն ու Արտաքին գործերի նախարարությանը` փնտրելով նրանց աջակցությունը սատարելու փխրուն հանրապետությանը, որի բնակչության մեծամասնությունը փախստականներ էին և 1915 թվականից հետո Օսմանյան կառավարության իրականացրած ցեղասպանությունից փրկվածներ: Սույն ուսումնասիրությունը նպատակ ունի քննելու թե ինչպես “Հայկական Հարցը”, որպես միջազգային համակարգում հայերի իրավական պահանջ, հասել էր Բրազիլիա և մտել Բրազիլիայի արտաքին քաղաքականության օրակարգ: Հայկական պահանջները քաղաքական օրակարգ էին ընդգրկվել [հարցով] հետաքրքրված մի փոքր խմբի միջոցով, ովքեր անձնական կապերի և մամուլի ինտենսիվ քարոզչության շնորհիվ հասանելիություն էին ձեռք բերել դեպի որոշում կայացնողները: Առաջին աշխարհամարտից հետո Բրազիլիան փորձում էր իր տեղը վերահաստատել միջազգային համակարգում որպես գլխավոր խաղացող: Այս համատեքստում Էթիէն Պրազիլի կողմից Հայկական հարցը ներկայացվում էր որպես հնարավորություն` ցույց տալու մեծ տերություններին, որ Բրազիլիան պատրաստ էր դիմակայելու ստեծված համաշխարհային նոր սցենարի մարտահրավերներին, և, հետևաբար, արժանի էր այն կարևոր տեղին, որին արժանացել էր 1919 թվականի Փարիզի խաղաղության վեհաժողովում և Ազգերի Լիգայում: Վարկածը կայանում է նրանում, որ Բրազիլական աջակցությունը Հայկական հարցին Պեսոայի վարչակազմի պրագմատիկ քայլն էր` համաշխարհային հեղինակություն շահելու համար օրակարգ բերելով մարդասիրություը: Սակայն սա տեղի չէր ունենում նախաձեռնողաբար: Բրազիլական կառավարությունը պատասխանել է Ռիո դե Ժանեյրոյում ապրող այս հայերի խմբի ճնշումներին և միջազգային ասպարեզում ամերիկյան քայլերին: Որպես այդպիսին, այս խումբն աշխատել է իբրև սփյուռքի մի մաս` գործելով որպես համահայկական ուժ, որը օգտվելով Բրազիլիայի քաղաքական ծակոտկենությունից, ազդեցություն է ունեցել քաղաքական օրակարգի վրա: Մեթոդաբանությունը բաղկացած է Բրազիլիայում և արտասահմանում գտնվող ֆայլերի և փաստաթղթերի վերլուծության միջոցով վերականգնելով հայերի և բրազիլացիների միջև եղած բանակցությունները` հասկանալ վերջինիս աջակցությունը միջազգային ամբիոններում, ինչպես նաև վերլուծության ենթարկել 1910-20-ականների Ռիո դե Ժանեյրոյի մամուլը, որը մի գործիք էր հանրային կարծիքը զգայունացնելու միջոցով մղել Բրազիլիային միջոցներ ձեռնարկել: 1920-ականների վերջին Բրազիլիան վերջապես ընդունում է հայերի և թուրքերի հակամարտության միջնորդի դերը` համակված ժամանակակից մարդասիրական գաղափարներով, սակայն առաջնորդվելով պրագմատիզմով և միջազգային համակարգում հեղինակություն ձեռք բերելու բաղձանքով:

Nos anos 1910, a causa armênia aportou no Brasil por meio do trabalho do intelectual Etienne Brasil na imprensa e em sociedades científicas no Rio de Janeiro que retratou os armênios como um povo cristão do Oriente, alvo de toda sorte de perseguições por parte dos turcos muçulmanos no Império Otomano. Lançando mão do discurso orientalista largamente difundido no pensamento ocidental no seu tempo, Etienne Brasil buscou sensibilizar o público-leitor e os tomadores de decisão brasileiros a apoiarem os armênios na luta pela criação da República Armênia, cuja independência aconteceu, por fim, em 1918. Assim, Etienne Brasil tornou-se representante diplomático da nova república no Brasil, o que deu a ele o ensejo para dirigir-se ao Catete e ao Itamaraty em busca do reconhecimento oficial brasileiro ao novo Estado e de apoio para sustentar a frágil república e sua população composta, majoritariamente, por refugiados, sobreviventes do genocídio executado pelo governo otomano a partir de 1915. O objetivo desta pesquisa é examinar como a chamada “causa armênia” – conjunto de reivindicações jurídicas do povo armênio no sistema internacional – chegou ao Brasil e tornou-se ponto de pauta na política externa brasileira. Interessa compreender como as demandas armênias foram inseridas nessa agenda por um grupo de interesse de tamanho reduzido, que conseguiu ter acesso aos tomadores de decisão por meio de conexões pessoais, intensa propaganda na imprensa e uma leitura da política internacional que indicava que o Brasil tentava se reposicionar no sistema internacional como um ator de primeiro escalão após a Grande Guerra. Nesse contexto, a causa armênia foi apresentada por Etienne Brasil e seus aliados como uma oportunidade para o governo Epitácio Pessoa mostrar às Potências que o país estava pronto para lidar com desafios no cenário global e era, portanto, merecedor do lugar de destaque que recebeu na Conferência de Paz de Paris em 1919 e na Liga das Nações. A hipótese sustentada é que o apoio brasileiro à causa armênia foi um ato pragmático do governo Epitácio Pessoa que buscava, por meio de uma pauta humanitarista, angariar prestígio para o Brasil no sistema internacional. Todavia, isso não se deu de maneira proativa. O governo brasileiro reagiu às pressões desse grupo de armênios radicados no Rio de Janeiro e aos movimentos dos EUA no cenário internacional. Desse modo, é crucial compreender como esse grupo funcionou como parte de uma diáspora, atuando como uma força transnacional e que conseguiu aproveitar a permeabilidade do sistema político brasileiro para inserir suas demandas. A metodologia consiste na análise de arquivos no Brasil e exterior a fim de reconstituir a negociação entre armênios e brasileiros para que esses últimos apoiassem as reivindicações dos primeiros nos fóruns internacionais, além da leitura minuciosa da imprensa carioca nos anos 1910-1920, instrumento de sensibilização da opinião pública para pressionar o Brasil a intervir. No final de 1920, o governo brasileiro aceitou, finalmente, atuar como mediador na pacificação da Armênia, balizado pelas ideias do humanitarismo moderno, mas guiado pelo pragmatismo, em busca de prestígio no sistema internacional.
Pragmatism and Humanitarianism: Brazilian foreign policy and the Armenian Cause (1912-1922)
Keywords: Brazilian foreign policy; Armenian Cause; Epitácio Pessoa; Etienne Brasil; Հայաստան; Բրազիլիայի արտաքին քաղաքականություն; Հայկական հարց; Էպիտասիո Պեսոա; Էթիէն Պրազիլ; Armênia; Política externa brasileira; Causa armênia; Epitácio Pessoa; Etienne Brasil; Armenia